2014
DOI: 10.1002/jaba.149
|View full text |Cite
|
Sign up to set email alerts
|

Comparing massed‐trial instruction, distributed‐trial instruction, and task interspersal to teach tacts to children with autism spectrum disorders

Abstract: Although massed-trial instruction, distributed-trial instruction, and task interspersal have been shown to be effective methods of teaching skills to children with autism spectrum disorders, they have not been directly compared. In the current study, we taught 6 children to tact shapes of countries using these methods to determine which would result in the quickest acquisition. Five of the 6 participants acquired the targets in the massed-trial condition before the other 2 conditions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
45
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 35 publications
(50 citation statements)
references
References 3 publications
2
45
0
Order By: Relevance
“…Majdalany et al () found that massed instruction (i.e., shorter intertrial intervals) was more efficient than distributed instruction for children with autism. Our study differed from Majdalany et al because we examined the distribution of practice sessions across days while keeping the duration of intertrial intervals consistent.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Majdalany et al () found that massed instruction (i.e., shorter intertrial intervals) was more efficient than distributed instruction for children with autism. Our study differed from Majdalany et al because we examined the distribution of practice sessions across days while keeping the duration of intertrial intervals consistent.…”
Section: Resultsmentioning
confidence: 99%
“…In contrast, Majdalany, Wilder, Greif, Mathisen, and Saini (2014) found that massed instruction with short periods between trials was more efficient than longer periods between trials within a session (i.e., distributed practice) for five of six children with autism. Nevertheless, these studies described massed and distributed practice as the intertrial interval between successive practice opportunities (e.g., trials conducted every 1 to 2 s vs. every 10 s; Majdalany et al, ), and not as the distribution of practice sessions across days of the week.…”
mentioning
confidence: 99%
“…For this reason, it is commonly recommended to deliver instructional trials at a rapid pace during DTT. Research fi ndings have shown that acquisition is enhanced with short (e.g., 2-s to 3-s) versus long (e.g., 10-s to 20-s) it is (e.g., Koegel, Dunlap, & Dyer, 1980 ;Majdalany et al, 2014 ). Some research, however, also suggests advantages to presenting additional instructional stimuli during ITIs (e.g., Loughrey, Betz, Majdalany, & Nicholson, 2014 ;Reichow & Wolery, 2011 ;Vladescu & Kodak, 2013 ).…”
Section: Intertrial Interval (Iti)mentioning
confidence: 93%
“…Authors have speculated that task interspersal procedures improve performance by functioning as a motivational operation (MO) . However, studies in which unknown targets were alternated with known targets have produced inconsistent fi ndings (see Benavides & Poulson, 2009 ;Charlop, Kurtz, & Milstein, 1992 ;Dunlap, 1984 ;Majdalany et al, 2014 ;Volkert et al, 2008 ). As such, the conditions under which task interspersal procedures are benefi cial have not yet been delineated and warrant further study.…”
Section: Task Interspersalmentioning
confidence: 94%
See 1 more Smart Citation